I.M. Copi y J.A. Gould (eds.), Contemporary Readings in Logical Theory - Fernando Bobbio (Crítica)
I.M. Copi y J.A. Gould (eds.), Contemporary Readings in Logical Theory, New York, The Macmillan Co., 1967, 342pp.